Are the drivers of production and sales of maize, groundnut, and soyabean by farming households in Malawi changing? Analysis of recent household surveys - Jolex, Aubrey; Benson, Todd (International Food Policy Research Institute, 2021)
By directing increasing shares of their farm production to the market and, thereby, realizing greater incomes, farming households can accelerate local rural economic development. In this study, we examine household and spatial factors that may drive smallholder farming households in Malawi to produce and sell maize, groundnut, and soyabean. Two cross-sectional analyses are done using household level data from rounds of the Malawi Integrated Household Survey (IHS). First, using data for farming households from the fifth IHS (2019/20) in a series of weighted logistical models, we examine which of a set of household and spatial level factors are associated with a household producing each of the three crops. For maize and groundnut, we extend the analysis by similarly identifying the factors associated with whether a producing household sells any of their maize or groundnut, and if, they do, whether they sell more than half of their harvest. The second analysis consists of replicating the logistical models for production and sales using household data from the fourth IHS (2016/17) and comparing those results to the results obtained from the fifth IHS. This is done to identify whether any drivers of the production and sale of the three crops are changing over time. Overall, only a few factors are consistently associated with a farming household choosing to produce a particular crop or to sell part of their production of the crop. We also see limited changes between 2016/17 and 2019/20 in the drivers of the production and sale of these crops. However, the strength of the positive associations between landholding size and the commercial production of the three crops intensified between the two surveys. This suggests that as landholdings become smaller with continuing population growth, commercial production will increasingly be limited to those households with the largest landholdings. Government and other stakeholders in rural economic development can consider the evidence from these analyses in developing strategies to foster greater diversity in employment in rural economies across Malawi away from agriculture, while nonetheless promoting increased production by those smallholders in a position to participate profitably in the value chains for these crops.